Effect of Blanket Warmer Use on Shivering Patients Post Regional Anesthesia: A Systematic Review - Pambudi Eko Prasetyo; Desiyani Nani; Ridlwan Kamaluddin (Green Publisher Indonesia, 2024)
Shivering is closely related to hypothermy and is one of the serious problems in surgical patients and can adversely affect the patient's condition. In addition, shivering is also considered an important clinical problem to get attention to, especially since it affects the patient's comfort and increases metabolic needs that can cause problems and complications in the cardiovascular. One of the non-pharmacological interventions that can be applied is the use of a blanket warmer. Evidence related to the application of blanket warmers to treat shivering in post-regional anesthesia patients is still limited, therefore, the author is interested in further reviewing the effectiveness of the use of blanket warmers for shivering patients in the form of a systematic review. To identify the effectiveness of blanket warmers against shivering in post-regional anesthesia patients based on evidence-based research. This research is a literature study with the PRISMA approach. Systematic review using PICO. The search databases used are Google Schoolar, Pub Med, Scince Direct, Wiley Online Liberary with the keywords blanket warmer, shivering, and regional anesthesia. Result: Based on 8 research articles reviewed, it was found that blanket warmers were shown to be effective in treating shivering in post-regional anesthesia patients. The intervention technique is applied using a warm blanket increasing the body temperature. The intervention group gained an average time faster compared to the control group. Blanket warmer interventions such as electric blanket warmer, water warmer blanket, blanket blower warmer, warm blanket significantly improve body temperature in shivering post regional anesthesia patients.